Is My Foreign Yours? The Concept of Foreignness in the Regulation of Political Finance. Issue 2 (3rd April 2019) - Orr, Graeme
ABSTRACT: Debates over 'foreign' political influence focus on the regulatory 'why' and 'how'. This masks deeper questions about 'who' is foreign. Is foreignness a factor of where money is housed or its owner's status? What of permanent residents and citizens abroad? This article unearths the debate in two stages. First, it analyses 'foreignness' as a general socio-legal concept linked to xenophobic wariness of, or outright aversion to others. Yet in modern liberal legal orders, outright discrimination is not an acceptable method or motivation for regulation. Instead, three distinctive, underlying conceptions of foreignness are identified within liberal legalism: jurisdiction, political community, and material interconnectedness. Application across five anglophone democracies shows that political finance law in each of those countries embodies aspects of every conception. Given they are distinguishable, this suggests not only that regulation in this area is still evolving normatively but, more importantly, that 'foreignness' is a rich conception not easily captured in a single definition. Revealingly, although foreignness is logically a nested and symmetric idea, regulation rarely touches influence between federal regions or actions of local corporations abroad.